2012
DOI: 10.1007/s00192-012-1709-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of postoperative urinary tract infection after uterosacral ligament suspension

Abstract: Patients requiring Foley catheter at discharge following vaginal prolapse repair are at highest risk for UTI and require prophylactic antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 5 publications
1
12
1
Order By: Relevance
“…1,2 Each year, UTIs account for more than 8.1 million visits to health care providers 3 and cost an estimated $1.6 billion in the United States alone. [5][6][7][8] The risk of UTI in this population ranges from 5% to 35% and is significantly increased with exposure to postoperative catheterization. [5][6][7][8] The risk of UTI in this population ranges from 5% to 35% and is significantly increased with exposure to postoperative catheterization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Each year, UTIs account for more than 8.1 million visits to health care providers 3 and cost an estimated $1.6 billion in the United States alone. [5][6][7][8] The risk of UTI in this population ranges from 5% to 35% and is significantly increased with exposure to postoperative catheterization. [5][6][7][8] The risk of UTI in this population ranges from 5% to 35% and is significantly increased with exposure to postoperative catheterization.…”
Section: Resultsmentioning
confidence: 99%
“…4 In the field of obstetrics and gynecology, UTI is one of the most common complications of pelvic reconstructive surgery, as is urinary retention. 5,[7][8][9][10][11][12][13][14][15] Urinary retention occurs in up to 50% of women undergoing pelvic floor surgery. 5,[7][8][9][10][11][12][13][14][15] Urinary retention occurs in up to 50% of women undergoing pelvic floor surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Rates of non- E.coli uropathogens have been reported in catheterized patients between 61 and 65% [16]. In a retrospective cohort of patients undergoing vaginal reconstructive surgery, prophylactic antibiotics decreased the risk of postoperative UTI in women requiring use of Foley catheterization at time of discharge [17]. This concept is further supported by Ghezzi et al [18] who reported prophylactic single-dose antibiotic therapy may help reduce the rate of UTIs after short-term urethral catheterization in women undergoing tension-free vaginal tape procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of UTI in these two studies was high. Urinary retention is a well‐established risk factor for UTI and the need for UTI treatment increases with duration of catheterization . Women in urinary retention who rely on catheterization for bladder‐emptying may harbor different pathogens or display higher bacterial counts.…”
Section: Discussionmentioning
confidence: 99%